Diagnóstico energético del sistema de distribución y calentamiento de agua del hotel El Libertador de la ciudad de Riobamba. Diseño de un plan de mejora de eficiencia energética para dar soluciones técnicas y económicamente viable.” - PALACIOS Almache, Juan Carlos (2019)
The El Libertador hotel located in the city of Riobamba has a heating and water distribution system that is oversized and does not have thermal insulation in its storage tanks, which causes low efficiency and high cost in the consumption of LPF fuel. The objective of this research is to improve the energy efficiency of the water heating system by modifying the current design to reduce conventional energy consumption. Initially, an energy audit was carries out to identify the energy consumers in the process, using a Pareto chart the process of heating and storage of hot water was selected since its consumes more than 90% of the energy. When the hotel is at its maximum capacity, the current system requires a power per day of 142,4 kW-h in the system and 54,53 kWh for loss in the storage tank. For the sizing of the equipment based on the NEC 11 standard, an energy consumption of 67,5 kW-h is obtained. It is proposed in the study to use solar collectors to meet the energy demand that the system requires, this change allows to improve energy efficiency since the collector tanks have a thermal insulation, reduce the cost of operation and reduce the consumption of conventional energy. An energy use indicator of 0,5680 is obtained and a cost of $ 0,03 to produce a kW-h. The initial investment is high, but a recovery is achieved with an IRR of 51,8% over a useful life of the equipment of 15 years.